Kerjasama Ekonomi Indonesia-China dan Sengketa Laut Natuna di Era Kepemimpinan Joko Widodo - Christina, Melany Putri Bella; Andaneswari, Annisa Kirana (Global and Policy Journal of International Relations, 2025)
Using a constructivist approach, this study seeks to explain the reason why China and Indonesia's economic cooperation has actually grown higher amidst their conflict over South China Sea. The SCS dispute has "dragged" Indonesia along with China claim over The Natuna Sea in the Riau Island which actually part of Indonesia’s Exclusive Economy Zone. The dispute intensified when China’s ships unlawfully entered Natuna waters in 2016 to conduct fishing operations. Ironically, economic cooperation between China and Indonesia has actually increased despite the dispute of Natuna Sea. Previously, United States and Japan were Indonesia’s main trading partners, but since 2016, China has taken their place. China is now leading as Indonesia's top trading partner. Moreover, China since 2016 has become the second largest investor for Indonesia after Singapore. Researchers assume that economic cooperation has become intense even in the midst of the SCS conflict because the two countries have interests driven by similar projection ideas about economic development and the closeness of identity between President Jokowi and President Xi Jinping. For constructivists, state interests are dynamic and  interests might change along with normative social interactions. This study uses a qualitative method with an emphasis on tracing conflict and cooperation data between the two countries. The data will be interpret further by using constructivist approach. Keyword: Economic Cooperation, Natuna Sea Conflict, Constructivism, Jokowi